Taper equations for Gmelina arborea in Omo forest reserve, southwestern Nigeria (2011)
Taper equations were generated for five diameter classes and four age series (11, 16, 21, and 26-year-old) in melina arborea plantations in Omo forest reserve, Nigeria. Three temporary sample plots of 20 m x 20 m were randomly selected from each age series. The diameter at the breast height (dbh) of all trees within each sample plot was measured and grouped into five dbh classes of 10–20 cm, 20–30 cm, 30–40 cm, 40–50 cm and 50 cm and above. The tree whose dbh was closest to the mean dbh of each diameter class was selected for further enumeration and felling. Before felling, the following measurements were made on each selected tree: diameter at the ground level (DG), diameters at 15 cm (D15), 30 cm (D30), and 45 cm (D45) above the ground and total height. After felling, the stump height (Hst) was measured and the log was sectioned into bolts after which the inside-back and outside-bark diameter of each bolt as well as the length were measured. Taper functions were then developed for each diameter class and age series. The taper function for the diameter classes were: , , , , for trees in 10–20 cm , 20–30 cm, 30 -40 cm, 40–50 cm and 50 cm and above diameter classes, respectively. The functions generated were assessed using F-ratio, Root Mean Square of Error (RMSE) and adjusted R-square (R2adj). The models were validated using t-test to compare the observed and predicted values. The taper functions generated in this study were found to be satisfactory based on the various criteria used for their assessment and validation. Thus, they are recommended for use in estimating the taper of Gmelina arborea trees.